The Effect of Individual and Group Sexual Skills Training on Sexual Satisfaction and Sexual Self-Esteem in Women: A Quasi-Experimental Study on the Effectiveness of Individual Sexual Skills Training on Sexual Satisfaction - Fadakar, Mahsa; Hesamy, Kajal; Shahoie, Roonak; Nouri, Bijan (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of this study was to compare the effects of individual and group training in sexual skills on sexual satisfaction and sexual self-esteem among women attending comprehensive health centers in Sanandaj. Methods: This quasi-experimental study was conducted on 60 women attending comprehensive health centers in Sanandaj, who were randomly assigned to three groups: individual training, group training, and control. Data collection tools included a demographic and obstetric questionnaire, the Hudson Sexual Satisfaction Questionnaire, and the Sexual Self-Esteem Inventory–Short Form (SSEI-W-SF). Data were collected according to the objectives of the study and analyzed using STATA version 12. The significance level was set at 0.05. Findings: Based on the results, all three study groups were homogeneous in terms of demographic and clinical characteristics. Four weeks after the intervention, the mean and standard deviation of sexual satisfaction in the individual training group showed a statistically significant difference (p < 0.05; p = 0.00). However, the mean satisfaction scores in the group training and control groups did not show a statistically significant difference. In all three groups, the mean and standard deviation of sexual self-esteem scores four weeks after training did not show a significant difference. Conclusion: The results of this study demonstrated that individual-based training leads to an increase in sexual satisfaction. Utilizing this educational approach in comprehensive health centers can enhance women’s sexual health and improve the dysfunctional cycle of family clinical relationships.